(untitled) (Orfeu, 2023)
Motivation is what leads a person to action and the study of this topic in music can help teachers establish a teaching environment in which their students can fully develop their musical abilities. The objective of this article was to verify through a systematic literature review how children and adolescents are motivated to learn music according to the self-determination and expectancy-value theories. In this research, 15 articles were selected. The reviewed studies pointed out that the satisfaction of basic psychological needs, the strengthening of intrinsic motives and the promotion of extrinsic motives, as well as students’ expectations and perception of the value of music influence their motivation to learn and their performance.